Cv Bipartite Entanglement of Non-Degenerate Three-Level Laser with Squeezed Modes Pumped by Coherent Light (Global Journal of Science Frontier Research, 2015)
We analyze the CV bipartite entanglement of the light generated by a coheretly pumped non degenerate three-level laser with a two-mode subharmonic generator coupled to a twomode vacuum reservoir via a single-port mirror, whose open cavity contains N non-degenerate three-level cascade atoms. We carry out our analysis by putting the noise operators associated with a vacuum reservoir in normal order. It is found that the photon-state of the system is strongly entangled at steady state where as the atom state of the system is not entangled. We have also shown that as the stimulated decay constant increases, the degree of entanglement increases. In addition, we have established that the photons in the laser cavity are highly correlated and the photon correlation and entanglement increases as the amplitude of the coherent light driving the pump mode increases. Moreover, we have realized that the presence of the subharmonic generator leads to an increase in the degree of entanglement and correlations.
Keywords: continuous variables; bipartite; entanglement; quadrature squeezing; correlations; twomode subharmonic generator